Onbegrensd = Unbegrenzt. - Hachmeister, Heiner (Machelen-aan-de-Leie : Roger Raveelmuseum Machelen-Zulte, 2004)
Albers, Josef ; Dierickx, Karel ; Ensor, James ; Fautrier, Jean ; Gliese, Carsten ; de Kooning, Willem ; Le Corbusier ; Morandi, Giorgio ; Picasso, Pablo ; Raveel, Roger ; Seitz, Gustav ; Soutter, Louis ; Tobey, Mark ; Wölfli, Adolf
bibliog. p. 77-79
Nederlands
Duits
Exhibition. Onbegrensd = Unbegrenzt. Roger Raveelmuseum Machelen-Zulte. 17.04.2004 - 06.06.2004
boek